2020
DOI: 10.3153/ar20009
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of ecological status in Tunca (Tundzha) River (Turkish Thrace) based on environmental conditions and bacterial features

Abstract: It is inevitable that the running waters which are used for a lot of different activities like fishing, irrigation, domestic water usage are under threat because of the settlements, industrial or agricultural activities. To provide the sustainable usage of these ecosystems we have to know their current features and their balance under changing environmental conditions. In the present study, the ecological status of Tunca (Tundzha) River which is located on Turkish Thrace was evaluated based on environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A maximum value of 135 mg L -1 was reported for NO 3 concentration in groundwater in Eskipazar region (Karabük) where the groundwater is used for drinking and domestic purposes (Keskin, 2010). Mimiroğlu et al (2020) showed that NO 3 concentration in drinking waters ranged from 0.12 to 19.30 mg L -1 across a rice-cultivated region in İpsala Township of Edirne and Davraz and Özdemir (2014) reported that approximately 20% of wellwater samples exceeded the recommended maximum allowable value of 50 mg NO3 L -1 in drinking water in Çelikli Plain (Burdur) where local people heavily depend on well water for drinking. Davraz et al (2016) reported that NO 3 concentrations in 37% of 50 well water samples exceeded 50 mg L -1 threshold for potable water set by WHO.…”
Section: Nitrates In Drinking Watersmentioning
confidence: 99%
“…A maximum value of 135 mg L -1 was reported for NO 3 concentration in groundwater in Eskipazar region (Karabük) where the groundwater is used for drinking and domestic purposes (Keskin, 2010). Mimiroğlu et al (2020) showed that NO 3 concentration in drinking waters ranged from 0.12 to 19.30 mg L -1 across a rice-cultivated region in İpsala Township of Edirne and Davraz and Özdemir (2014) reported that approximately 20% of wellwater samples exceeded the recommended maximum allowable value of 50 mg NO3 L -1 in drinking water in Çelikli Plain (Burdur) where local people heavily depend on well water for drinking. Davraz et al (2016) reported that NO 3 concentrations in 37% of 50 well water samples exceeded 50 mg L -1 threshold for potable water set by WHO.…”
Section: Nitrates In Drinking Watersmentioning
confidence: 99%